Benefits of individual special strength training model for touch pass excellence in elite football - Privalov, A. V.; Nifontov, M. Y.; Vishnyakova, Yu. Yu.; Mukhamedzanov, R. R. (Theory and Practice of Physical Culture, 2020)
Objective of the study was to develop and test benefits of a special strength training model for touch pass excellence in elite football with the relevant field zone control trainings using special strength training machines.